THE TRANFORMATION OF BEING TRANSGENDER INTO TRANSSEXUAL IN THE DANISH GIRL NOVEL BY DAVID EBERSHOFF - Tira Mariana; Nindi Eliska Safitri; Firdiansyah (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
The study discusses the transformation of a man to become a transgender then to transsexual in The Danish Girl novel by David Ebershoff. This study aims to find out how are the process or the transformation journey of an individual to became transgender then to become a transsexual experienced by the male main character. This study is a fiction- based research which uses close-reading technique analysis and applied Queer Theory to answer the research question. The result of study found that there are 6 transformation process of being transgender into transexual. They are being a female model, started to wear woman clothes as a model, feeling comfortable and wear ladies dress secretly, feeling as a women, dressing up and behaving a like a woman in public, having romantic relationship with a man, having genital operation to perfect gender.